Block copolymer
The introduction of a block copolymer with fully aromatic polyamide and flexible chain polymer blocks addresses the adhesion challenges in nonaqueous electrolyte secondary battery separators, resulting in improved battery performance and safety.
Patent Information
- Application Number
- JP2023178459
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-28
AI Technical Summary
Existing separators for nonaqueous electrolyte secondary batteries, particularly lithium-ion batteries, face challenges with adhesion, which affects the performance and reliability of the batteries.
A block copolymer is developed, comprising a fully aromatic polyamide block A and a flexible chain polymer block B, which is used to create an adhesive layer for the batteries. This block copolymer enhances the adhesion properties between the separator and the electrodes.
The use of the block copolymer-based adhesive layer significantly improves the adhesion between the separator and the electrodes, leading to enhanced battery performance, reliability, and safety by preventing minute short circuits.
Smart Images

Figure 2025068505000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a block copolymer. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, particularly lithium ion secondary batteries, are widely used as batteries for personal computers, mobile phones, personal digital assistants, and in-vehicle applications due to their high energy density. Lithium ion batteries usually have a separator between the positive electrode and the negative electrode, and various separators have been proposed. For example, Patent Document 1 discloses a separator for secondary batteries in which a first porous layer having a shutdown property and a second porous layer containing an aramid resin and an inorganic material are laminated. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2006-299612 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the above-mentioned conventional techniques have room for improvement in adhesiveness. One aspect of the present invention has been made in consideration of the above, and has an object to provide, for example, a novel block copolymer that can impart adhesiveness to an adhesive layer for a non-aqueous electrolyte secondary battery. [Means for solving the problem]
[0005] The present invention includes the following aspects. <1> A block copolymer having a block A mainly composed of a unit represented by the following formula (1) and a block B mainly composed of a unit represented by the following formula (2a) and / or formula (2b): -(NH-Ar1-NHCO-Ar2-CO)- Formula (1) -(NH-B1-NHCO-B2-CO)- Formula (2a) -(NH-B3-NHCONH-B4-NHCO)- Formula (2b) In formula (1), Between different units, the structures of Ar1 and Ar2 may be different. Ar1 and Ar2 each independently represent a divalent group having one or more aromatic rings. In formula (2a), Between different units, the structures of B1 and B2 may be different, At least one of B1 and B2 is a divalent group not having an aromatic ring, In formula (2b), Between different units, the structure of each of B3 and B4 may be different, At least one of B3 and B4 is a divalent group not having an aromatic ring. <2> The proportion of the block A in the entire block copolymer molecule is 10 to 70 mol %. <1> The block copolymer according to claim 1. <3> The proportion of the block B in the entire block copolymer molecule is 30 to 90 mol %. <1> or <2> The block copolymer according to claim 1. <4> <1> ~ <3> 13. An adhesive layer for a non-aqueous electrolyte secondary battery, comprising the block copolymer according to claim 12. <5> Further comprising a filler, <4> The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1. <6> On one or both sides of the polyolefin porous film, <4> or <5> 2. A laminate separator for a non-aqueous electrolyte secondary battery, comprising the adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1 laminated thereon. <7> A positive electrode and <4> or <5> The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1, A negative electrode; are laminated in this order. <8> A positive electrode and <6> The laminate separator for a nonaqueous electrolyte secondary battery according to claim 1, A negative electrode; are laminated in this order. <9> <4> or <5> The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1, <6> The laminate separator for a non-aqueous electrolyte secondary battery according to claim 1, <7> or <8> A non-aqueous electrolyte secondary battery comprising the member for a non-aqueous electrolyte secondary battery according to claim 1. Effect of the Invention
[0006] According to one aspect of the present invention, an adhesive layer for a non-aqueous electrolyte secondary battery is provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to this, and various modifications are possible within the scope described, and embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more, B or less."
[0008] [1. Block Copolymers] [Block copolymer structure] A block copolymer according to one embodiment of the present invention has a block A mainly composed of a unit represented by the following formula (1). In this specification, "mainly composed of a unit represented by formula (1)" means that the proportion of the units represented by formula (1) among all the units contained in block A is more than 50%. -(NH-Ar1-NHCO-Ar2-CO)- Formula (1)
[0009] In formula (1), Ar1 and Ar2 are each independently a divalent group having one or more aromatic rings. The block copolymer may contain a plurality of units represented by formula (1). In this case, the structures of Ar1 and Ar2 may be different between different units.
[0010] Ar1 and Ar2 may have an unsubstituted aromatic ring, a substituted aromatic ring, or a combination of an unsubstituted aromatic ring and a substituted aromatic ring. An aromatic ring refers to a cyclic compound that satisfies the Hückel rule. Examples of aromatic rings include benzene, naphthalene, anthracene, azulene, pyrrole, pyridine, furan, and thiophene. In one embodiment of the present invention, the aromatic ring is composed of only carbon atoms and hydrogen atoms. In one embodiment of the present invention, the aromatic ring is a benzene ring or a condensed ring of two or more benzene rings (such as naphthalene and anthracene).
[0011] Examples of the substituent that the aromatic ring may have include an alkyl group, an alkenyl group, an alkynyl group, a cycloalkyl group, a cycloalkenyl group, a cycloalkynyl group, a hydroxyl group, a carboxyl group, a nitro group, an amino group, a halogen group, and a sulfonic acid group. When the substituent has a carbon atom, the number of carbon atoms contained in one substituent may be 1 to 20, 1 to 15, or 1 to 10.
[0012] Block A is a wholly aromatic polyamide block. The ratio of the units represented by formula (1) to all the units contained in block A is preferably 50% or more, more preferably 70% or more, and even more preferably 90% or more. In one embodiment, all the units contained in block A may be the units represented by formula (1) except for the terminals.
[0013] Furthermore, the block copolymer according to one embodiment of the present invention has a block B mainly composed of units represented by formula (2a) and / or formula (2b). In this specification, "mainly composed of units represented by formula (2a) and / or formula (2b)" means that the proportion of units represented by formula (2a) and / or formula (2b) among all units contained in block B is more than 50%. -(NH-B1-NHCO-B2-CO)- Formula (2a) -(NH-B3-NHCONH-B4-NHCO)- Formula (2b)
[0014] In formula (2a), at least one of B1 and B2 is a divalent group having no aromatic ring. The divalent group having no aromatic ring may be a divalent group having 2 or more, 3 or more, or 4 or more carbon atoms, or may be a divalent group having 20 or less, 15 or less, or 10 or less carbon atoms. More specifically, the divalent group having no aromatic ring is, for example, a divalent group formed by linking 2 to 10 methylene groups or oxyethylene groups. The block copolymer may contain a plurality of units represented by formula (2a). In this case, the structures of B1 and B2 may be different between different units.
[0015] In formula (2b), at least one of B3 and B4 is a divalent group having no aromatic ring. The divalent group having no aromatic ring may be a divalent group having 2 or more, 3 or more, or 4 or more carbon atoms, or may be a divalent group having 20 or less, 15 or less, or 10 or less carbon atoms. More specifically, the divalent group having no aromatic ring is, for example, a divalent group formed by linking 2 to 10 methylene groups or oxyethylene groups. The block copolymer may contain a plurality of units represented by formula (2b). In this case, the structures of B3 and B4 may be different between different units.
[0016] The main component of block B may include only the unit represented by formula (2a), may include only the unit represented by formula (2b), or may include both the units represented by formula (2a) and formula (2b). The ratio of the units represented by formula (2a) and / or formula (2b) among all the units included in block B is preferably 50% or more, more preferably 70% or more, and even more preferably 90% or more. In one embodiment, all the units included in block B may be the units represented by formula (2a) and / or formula (2b) except for the terminals. Here, in the present specification, block B may also be referred to as a flexible chain polymer block. Examples of flexible chain polymers constituting the flexible chain polymer block include semi-aromatic polymers (semi-aromatic polyamide, semi-aromatic polyurea, semi-aromatic polyurethane, etc.) and aliphatic polymers (aliphatic polyamide, aliphatic polyurea, aliphatic polyurethane, etc.). In the present specification, the "semi-aromatic polymer" may be a polymer composed of a monomer having an aromatic ring and a monomer not having an aromatic ring. In this specification, the term "aliphatic polymer" includes a polymer consisting only of monomers that do not have an aromatic ring.
[0017] Examples of monomers that do not have an aromatic ring and that constitute flexible chain polymers include diamines in which two amino groups are bonded by a hydrocarbon chain (trimethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, etc.); diamines in which two amino groups are bonded by a polyether (1,2-bis(2-aminoethoxy)ethane, 1,3-bis(3-aminopropoxy)ethane, etc.); and dicarboxylic acid halides in which two carboxylic acid halide groups are bonded by a hydrocarbon chain (succinic acid dichloride, glutaric acid dichloride, adipic acid dichloride, pimelic acid dichloride, suberic acid dichloride, azelaic acid dichloride, sebacic acid dichloride, etc.). diisocyanates in which two carboxylic acid halide groups are linked by a polyether; diisocyanates in which two isocyanate groups are linked by a hydrocarbon chain (e.g., trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, heptamethylene diisocyanate, octamethylene diisocyanate, 1,6-diisocyanato-2,4-dimethylhexane, 1,9-diisocyanato-5-methylnonane, etc.); diisocyanates in which two isocyanate groups are linked by a polyether (e.g., 1,10-dioxa-4,7-dioxa-2,9-diazadeca-1,9-diene, 1,2-bis(3-isocyanatopropyloxy)propane, etc.).
[0018] Block A and block B can be linked by an amide bond. In this specification, the term "amide bond" refers to a moiety having the structure -NH-C(=O)- (the hydrogen bonded to the nitrogen atom may be substituted with a hydrocarbon group or the like). An example of a polymer having many amide bonds is polyamide [-(NH-R-NH-C(=O)-R'-C(=O)) n -], polyurea [-(NH-R-NH-C(=O)-NH-R'-NH-C(=O)) n -], polyurethane [-(C(=O)-NH-R-NH-(C=O)-O-R'-O) n -] are some examples.
[0019] The block configuration of the block copolymer is not particularly limited. In one embodiment, the block copolymer may be a diblock copolymer of block A-block B. In one embodiment, the block copolymer may be a triblock copolymer of block A-block B-block A or block B-block A-block B. In one embodiment, the block copolymer has four or more blocks (e.g., a tetrablock copolymer of block A-block B-block A-block B).
[0020] The lower limit of the proportion of block A in the entire block copolymer molecule is preferably 10 mol % or more, more preferably 15 mol % or more, and even more preferably 20 mol % or more. The upper limit of the proportion of block A in the entire block copolymer molecule is preferably 70 mol % or less, more preferably 60 mol % or less, and even more preferably 50 mol % or less. The lower limit of the proportion of block B in the entire block copolymer molecule is preferably 30 mol % or more, more preferably 40 mol % or more, even more preferably 45 mol % or more, and even more preferably 50 mol % or more. The upper limit of the proportion of block B in the entire block copolymer molecule is preferably 90 mol % or less, more preferably 85 mol % or less, and even more preferably 80 mol % or less. If the proportions of block A and block B are within the above ranges, the polymer is likely to be suitable for use in an adhesive layer for a nonaqueous electrolyte secondary battery, as described below.
[0021] The lower limit of the number of units represented by formula (1) contained in one block A is preferably 10 or more, and more preferably 20 or more. The upper limit of the number of units represented by formula (1) contained in one block A is, for example, 1000 or less, 500 or less, or 300 or less. In one embodiment, at least one of the blocks A contained in the block copolymer is a block A that satisfies the above-mentioned conditions. In one embodiment, all of the blocks A contained in the block copolymer are blocks A that satisfy the above-mentioned conditions.
[0022] The lower limit of the number of units represented by formula (2a) and / or formula (2b) contained in one block B is preferably 5 or more, more preferably 10 or more, and even more preferably 15 or more. The upper limit of the number of units represented by formula (1) contained in one block B is, for example, 500 or less, 300 or less, or 200 or less. In one embodiment, at least one of the blocks B contained in the block copolymer is a block B that satisfies the above-mentioned conditions. In one embodiment, all of the blocks B contained in the block copolymer are blocks B that satisfy the above-mentioned conditions.
[0023] [Method of manufacturing block copolymer] The block copolymer can be produced, for example, according to the following procedure. However, the method for producing the block copolymer is not limited to the method described below, and a person skilled in the art can produce the block copolymer by various methods by referring to the description of the present specification and common general technical knowledge.
[0024] (Production Example 1) (1A) A monomer represented by NH2-Ar1-NH2 and a monomer represented by XOC-Ar2-COX (X is a halogen atom) are used as monomers and polymerized according to a known aromatic polyamide polymerization method, thereby synthesizing a block A having a unit represented by formula (1). (2A) After the synthesis of block A is completed, a monomer represented by NH2-B1-NH2 is added to a solution containing block A and completely dissolved. (3A) A monomer represented by XOC-B2-COX (X is a halogen atom) is added to the solution obtained in step (2A) and reacted. This synthesizes block B having a unit represented by formula (2a) linked to block A. In this way, a block copolymer (block B-block A-block B) can be produced.
[0025] (Production Example 2) (1B) A monomer represented by NH2-B1-NH2 and a monomer represented by XOC-B2-COX (X is a halogen atom) are polymerized according to a known polyamide polymerization method, thereby synthesizing a block B having a unit represented by formula (2a). (2B) After the synthesis of block B is completed, a monomer represented by NH2-Ar1-NH2 is added to a solution containing block B and completely dissolved. (3B) A monomer represented by XOC-Ar2-COX (X is a halogen atom) is added to the solution obtained in step (2B) and reacted. This synthesizes block A having a unit represented by formula (1) linked to block B. In this way, a block copolymer (block A-block B-block A) can be produced.
[0026] (Production Example 3) (1C) A monomer represented by NH2-Ar1-NH2 and a monomer represented by XOC-Ar2-COX (X is a halogen atom) are used as monomers and polymerized according to a known aromatic polyamide polymerization method, thereby synthesizing a block A having a unit represented by formula (1). (2C) After the synthesis of block A is completed, a monomer represented by NH2-B3-NH2 is added to a solution containing block A and completely dissolved. (3C) The monomer represented by OCN-B4-NCO is added to the solution obtained in step (2C) and reacted. This synthesizes block B having a unit represented by formula (2b) linked to block A. In this way, a block copolymer (block B-block A-block B) can be produced.
[0027] (Production Example 4) (1D) A monomer represented by NH2-B3-NH2 and a monomer represented by OCN-B4-NCO are polymerized according to a known polyamide polymerization method, thereby synthesizing a block B having a unit represented by formula (2b). (2D) After the synthesis of block B is completed, a monomer represented by NH2-Ar1-NH2 is added to a solution containing block B and completely dissolved. (3D) A monomer represented by XOC-Ar2-COX (X is a halogen atom) is added to the solution obtained in step (2D) and reacted. This synthesizes block A having a unit represented by formula (1) linked to block B. In this way, a block copolymer (block A-block B-block A) can be produced.
[0028] In the above Production Examples 1 to 4, Ar1 contained in the monomer represented by NH2-Ar1-NH2 and Ar2 contained in the monomer represented by XOC-Ar2-COX are both defined as above. In one embodiment, the monomer represented by NH2-Ar1-NH2 is paraphenylenediamine, and the monomer represented by XOC-Ar2-COX is terephthalic acid dichloride.
[0029] In the above Production Examples 1 to 4, B1 contained in the monomer represented by NH2-B1-NH2 follows the above-mentioned definition. Also, B2 contained in the monomer represented by XOC-B2-COX follows the above-mentioned definition. In one embodiment, the monomer represented by NH2-B1-NH2 is hexamethylenediamine or 1,2-bis(2-aminoethoxy)ethane. In one embodiment, the monomer represented by XOC-B2-COX is terephthalic acid dichloride or sebacic acid dichloride.
[0030] In the above Production Examples 1 to 4, B3 contained in the monomer represented by NH2-B3-NH2 follows the above-mentioned definition. Also, B4 contained in the monomer represented by OCN-B4-NCO follows the above-mentioned definition. In one embodiment, the monomer represented by NH2-B3-NH2 is O,O'-bis(2-aminopropyl)polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol or 1,2-bis(2-aminoethoxy)ethane, and the monomer represented by OCN-B4-NCO is hexamethylene diisocyanate.
[0031] [2. Adhesive layer for non-aqueous electrolyte secondary battery] The adhesive layer for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention contains the block copolymer described above. By containing the block copolymer, the resulting layer exhibits adhesiveness and functions as an adhesive layer. Such adhesiveness is not observed in a layer containing only a wholly aromatic polymer (wholly aromatic polyamide) as a resin component. However, the adhesive layer may have a function other than adhesiveness (such as heat resistance). For example, the adhesive layer may also be a heat-resistant layer at the same time. Here, in this specification, the adhesive layer for a non-aqueous electrolyte secondary battery is also simply referred to as an "adhesive layer".
[0032] In one embodiment, the adhesive layer may include a filler. Examples of the filler include organic fillers and inorganic fillers. Among these, inorganic fillers are preferred.
[0033] The inorganic filler is preferably made of one or more inorganic oxides selected from the group consisting of silica, calcium oxide, magnesium oxide, titanium oxide, alumina, mica, zeolite, aluminum hydroxide, boehmite, etc. In order to improve the water absorption of the inorganic filler, the surface of the inorganic filler may be subjected to a hydrophilic treatment with a silane coupling agent, etc.
[0034] The upper limit of the particle size of the inorganic filler contained in the adhesive layer is preferably 1.0 μm or less, and more preferably 0.8 μm or less, from the viewpoint of making it possible to reduce the thickness of the laminated separator, and the lower limit of the particle size of the inorganic filler in the adhesive layer is preferably 0.005 μm or more, and more preferably 0.010 μm or more, from the viewpoint of making it possible to form the pore structure of the laminated separator.
[0035] Here, the average particle size of the inorganic filler is the average value of the equivalent sphere particle size of 50 inorganic fillers. The equivalent sphere particle size of the inorganic filler is a value actually measured by a transmission electron microscope. An example of a specific measurement method is as follows. 1. Using a transmission electron microscope (TEM; JEOL Ltd., JEM-2100F), images were taken at an accelerating voltage of 200 kV and a magnification of 10,000x using a Gatan Imaging Filter. 2. Using image analysis software (ImageJ), trace the particle contours of the obtained images and measure the spherical equivalent particle size of the inorganic filler particles (primary particles). 3. The above measurement is carried out on 50 randomly selected inorganic filler particles. The arithmetic mean of the spherical equivalent diameters of the 50 inorganic filler particles is taken as the average particle diameter of the particles.
[0036] The upper limit of the inorganic filler content in the adhesive layer is 70% by weight or less, preferably 65% by weight or less, more preferably 60% by weight or less, and even more preferably 55% by weight or less, when the total weight of the adhesive layer is 100% by weight. If the inorganic filler content is 70% by weight or less, the occurrence of mutual adhesion between separators can be reduced. The lower limit of the inorganic filler content in the adhesive layer is not particularly limited, and may be, for example, 0% by weight or more, more than 0% by weight, 10% by weight or more, 20% by weight or more, or 33% by weight or more. From the viewpoint of air permeability, the inorganic filler content in the adhesive layer is preferably 50% by weight or more.
[0037] [Method of manufacturing adhesive layer] The adhesive layer can be formed using a coating liquid obtained by dissolving or dispersing the resin component constituting the adhesive layer in a solvent. Also, the adhesive layer containing the resin component and the inorganic filler can be formed using a coating liquid obtained by dissolving or dispersing the resin component in a solvent and dispersing the inorganic filler.
[0038] The solvent may be a solvent that dissolves the resin component. The solvent may be a dispersion medium that disperses the resin component or the inorganic filler. Examples of the method for forming the coating liquid include a mechanical stirring method, an ultrasonic dispersion method, a high-pressure dispersion method, and a media dispersion method.
[0039] Examples of methods for forming the adhesive layer include a method in which the coating liquid is directly applied to the surface of a substrate and then the solvent is removed; a method in which the coating liquid is applied to a suitable support and then the solvent is removed to form the adhesive layer, the adhesive layer and the substrate are pressure-bonded together, and then the substrate is peeled off; a method in which the coating liquid is applied to a suitable support and then the substrate is pressure-bonded to the coating surface, and then the substrate is peeled off and then the solvent is removed; and a method in which the substrate is dip-coated by immersing it in the coating liquid and then the solvent is removed.
[0040] The solvent is preferably a solvent that does not adversely affect the substrate, dissolves the resin component uniformly and stably, and disperses the inorganic filler uniformly and stably. Examples of the solvent include one or more solvents selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, acetone, water, and the like.
[0041] The coating liquid may appropriately contain a dispersant, a plasticizer, a surfactant, a pH adjuster, and the like as components other than the resin component and the inorganic filler.
[0042] The coating liquid can be applied to the substrate by any conventional method. Specific examples of the method include a gravure coater method, a dip coater method, a bar coater method, and a die coater method.
[0043] When the coating liquid contains an aramid resin, the aramid resin can be precipitated by applying moisture to the coating surface, thereby forming the adhesive layer.
[0044] Examples of a method for removing the solvent from the coating liquid applied to the substrate include a method for removing the solvent from a coating film, which is a film of the coating liquid, by ventilation drying, heat drying, or the like.
[0045] In addition, by changing the amount of the solvent in the coating liquid, the porosity and average pore size of the resulting adhesive layer can be adjusted.
[0046] A suitable solid content concentration of the coating liquid may vary depending on the type of inorganic filler, but is generally preferably more than 3% by weight and not more than 40% by weight.
[0047] The coating shear rate when the coating liquid is applied onto the substrate may vary depending on the type of inorganic filler, but is generally preferably 2 (1 / s) or more, and more preferably 4 (1 / s) to 50 (1 / s).
[0048] [3. Laminated separator for non-aqueous electrolyte secondary batteries] The laminated separator according to one embodiment of the present invention has the adhesive layer laminated on one or both sides of the polyolefin porous film. The laminated separator may have a heat-resistant layer on one or both sides of the polyolefin porous film as an optional configuration.
[0049] In this specification, the polyolefin porous film is also referred to as a "polyolefin-based substrate", and is a substrate mainly composed of a polyolefin-based resin. "Mainly composed of a polyolefin-based resin" means that the ratio of the polyolefin-based resin in the substrate is 50% by weight or more, preferably 90% by weight or more, and more preferably 95% by weight or more of the total material constituting the substrate. The polyolefin-based substrate is mainly composed of a polyolefin-based resin and has many interconnected pores inside, allowing gas and liquid to pass from one side to the other side.
[0050] The polyolefin has a weight average molecular weight of 5×10 5 ~15×10 6 In particular, it is more preferable that the polyolefin contains a high molecular weight component having a weight average molecular weight of 1,000,000 or more, since this improves the strength of the laminate separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention.
[0051] The polyolefin may be, for example, a homopolymer or a copolymer obtained by polymerizing monomers such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, and 1-hexene.
[0052] Examples of the homopolymer include polyethylene, polypropylene, and polybutene, and examples of the copolymer include an ethylene-propylene copolymer.
[0053] Among these, polyethylene is more preferable as the polyolefin because it can prevent the flow of excessive current at a lower temperature. Note that "preventing the flow of excessive current" is also called "shutdown."
[0054] Examples of the polyethylene include low-density polyethylene, high-density polyethylene, linear polyethylene (ethylene-α-olefin copolymer), ultra-high molecular weight polyethylene having a weight-average molecular weight of 1,000,000 or more, etc. Among these, the polyethylene is more preferably ultra-high molecular weight polyethylene having a weight-average molecular weight of 1,000,000 or more.
[0055] The basis weight of the substrate can be appropriately determined in consideration of the strength, film thickness, weight, and handleability. However, in order to increase the weight energy density and volume energy density of the nonaqueous electrolyte secondary battery, the basis weight is preferably 2 to 20 g / m 2 is preferably 2 to 12 g / m 2 More preferably, the thickness is 3 to 10 g / m 2 It is even more preferable that:
[0056] The air permeability of the substrate is preferably 30 to 500 s / 100 mL, more preferably 50 to 300 s / 100 mL, in terms of Gurley value. When the substrate has an air permeability within the above range, the substrate can obtain sufficient ion permeability.
[0057] The porosity of the substrate is preferably 20 to 80% by volume, and more preferably 30 to 75% by volume, in order to increase the amount of electrolyte retained and to obtain the function of reliably preventing the flow of excessive current at lower temperatures.
[0058] In addition, the pore size of the pores in the substrate is preferably 0.3 μm or less, and more preferably 0.14 μm or less, so as to obtain sufficient ion permeability and prevent particles from entering the positive electrode and negative electrode.
[0059] The lower limit of the thickness of the substrate is preferably 4 μm or more, more preferably 5 μm or more, and even more preferably 6 μm or more. The upper limit of the thickness of the substrate is preferably 29 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. Examples of combinations of the lower limit and upper limit of the thickness of the substrate include 4 to 29 μm, 5 to 20 μm, and 6 to 15 μm.
[0060] [Manufacturing method of laminated separator] The method for producing the polyolefin-based substrate can be, for example, the following method. That is, first, a polyolefin-based resin, a pore-forming agent such as an inorganic filler or a plasticizer, and optionally an antioxidant, etc. are kneaded to obtain a polyolefin-based resin composition. Then, the polyolefin-based resin composition is extruded to prepare a sheet-shaped polyolefin-based resin composition. Then, the pore-forming agent is removed from the sheet-shaped polyolefin-based resin composition with an appropriate solvent. Then, the polyolefin-based resin composition from which the pore-forming agent has been removed is stretched to produce a polyolefin-based substrate.
[0061] The inorganic filler is not particularly limited, and examples thereof include inorganic fillers, specifically calcium carbonate, etc. The plasticizer is not particularly limited, and examples thereof include low molecular weight hydrocarbons such as liquid paraffin.
[0062] The method for producing the polyolefin-based substrate can include, for example, a method including the steps described below.
[0063] (i) a step of kneading ultra-high molecular weight polyethylene having a weight average molecular weight of 1 million or more, low molecular weight polyethylene having a weight average molecular weight of 10,000 or less, a pore-forming agent such as calcium carbonate or a plasticizer, and an antioxidant to obtain a polyolefin-based resin composition, (ii) a step of gradually cooling the obtained polyolefin-based resin composition and forming a sheet, (iii) a step of removing the pore-forming agent from the obtained sheet with an appropriate solvent, and (iv) a step of stretching the sheet from which the pore-forming agent has been removed at an appropriate stretch ratio.
[0064] In the method for producing an adhesive layer described in Section [2], if the substrate is a polyolefin porous film, the above-mentioned laminated separator can be produced.
[0065] [Physical properties of laminated separator] The adhesive strength between the laminated separator and the electrode (preferably the positive electrode) is preferably 0.5 N / m or more. If the adhesive strength is within the above range, it can be said that the adhesive layer functions sufficiently. For a specific method for measuring the adhesive strength, please refer to the examples of this application.
[0066] The laminate separator preferably has a heat shape retention rate in the MD direction of 90% or more. In this specification, the term "heat shape retention rate" refers to a parameter that indicates the degree to which an object can maintain its pre-heated shape when heated. For a specific method for measuring the heat shape retention rate, see the examples of this application. If the heat shape retention rate is within the above range, it can be said to have excellent heat resistance.
[0067] 4. Non-aqueous electrolyte secondary battery components and non-aqueous electrolyte secondary batteries The nonaqueous electrolyte secondary battery member according to one embodiment of the present invention may have a positive electrode, the above-mentioned adhesive layer for nonaqueous electrolyte secondary batteries, and a negative electrode laminated in this order. Alternatively, the nonaqueous electrolyte secondary battery member according to one embodiment of the present invention may have a positive electrode, the above-mentioned laminate separator for nonaqueous electrolyte secondary batteries, and a negative electrode laminated in this order. The nonaqueous electrolyte secondary battery according to one embodiment of the present invention includes the above-mentioned adhesive layer for nonaqueous electrolyte secondary batteries, the above-mentioned laminate separator for nonaqueous electrolyte secondary batteries, or the above-mentioned member for nonaqueous electrolyte secondary batteries.
[0068] The shape of the nonaqueous electrolyte secondary battery is not particularly limited, and may be a thin plate (paper) type, a disk type, a cylinder type, a prismatic type such as a rectangular parallelepiped, etc. The nonaqueous electrolyte secondary battery is, for example, a nonaqueous electrolyte secondary battery that obtains electromotive force by doping and dedoping lithium, and includes a nonaqueous electrolyte secondary battery member in which a positive electrode, the above-mentioned separator, and a negative electrode are laminated in this order. Note that the components of the nonaqueous electrolyte secondary battery other than the above-mentioned separator are not limited to the components described below.
[0069] The nonaqueous electrolyte secondary battery generally has a structure in which a battery element, in which a negative electrode and a positive electrode are opposed to each other via the separator described above and an electrolyte is impregnated in the structure, is enclosed in an exterior material. Note that the term "doping" refers to occlusion, support, adsorption, or insertion, and refers to the phenomenon in which lithium ions enter the active material of an electrode such as a positive electrode.
[0070] Since the nonaqueous electrolyte secondary battery member includes the above-mentioned separator, when the nonaqueous electrolyte secondary battery member is incorporated therein, the occurrence of micro-short circuits in the nonaqueous electrolyte secondary battery can be suppressed and the safety of the battery can be improved. Furthermore, since the nonaqueous electrolyte secondary battery includes the above-mentioned separator, the occurrence of micro-short circuits is suppressed and the battery has excellent safety.
[0071] [Positive electrode] The positive electrode in one embodiment of the present invention is not particularly limited as long as it is generally used as a positive electrode of a non-aqueous electrolyte secondary battery. For example, a positive electrode sheet having a structure in which an active material layer containing a positive electrode active material and a binder is formed on a positive electrode current collector can be used as the positive electrode. The active material layer may further contain a conductive agent and / or a binder.
[0072] The positive electrode active material may be, for example, a material capable of doping and dedoping lithium ions, specifically, a lithium composite oxide containing at least one transition metal such as V, Mn, Fe, Co, or Ni.
[0073] Examples of the conductive agent include carbonaceous materials such as natural graphite, artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and organic polymer compound sintered bodies. The conductive agent may be used alone or in combination of two or more kinds.
[0074] Examples of the binder include fluorine-based resins such as polyvinylidene fluoride (PVDF), acrylic resins, and styrene-butadiene rubber. The binder also functions as a thickener.
[0075] Examples of the positive electrode current collector include conductors such as Al, Ni, stainless steel, etc. Among them, Al is more preferable because it is easy to process into a thin film and is inexpensive.
[0076] Examples of methods for producing a positive electrode sheet include a method of pressurizing and molding a positive electrode active material, a conductive agent, and a binder on a positive electrode current collector; a method of forming a paste of a positive electrode active material, a conductive agent, and a binder using an appropriate organic solvent, applying the paste to a positive electrode current collector, drying the paste, and then applying pressure to adhere the paste to the positive electrode current collector.
[0077] [Negative electrode] The negative electrode in one embodiment of the present invention is not particularly limited as long as it is generally used as a negative electrode of a non-aqueous electrolyte secondary battery. For example, a negative electrode sheet having a structure in which an active material layer containing a negative electrode active material and a binder is formed on a negative electrode current collector can be used as the negative electrode. The active material layer may further contain a conductive agent and / or a binder.
[0078] The negative electrode active material may be, for example, a material capable of doping and dedoping lithium ions. Examples of such materials include carbonaceous materials. Examples of carbonaceous materials include natural graphite, artificial graphite, cokes, carbon black, and pyrolytic carbons.
[0079] The negative electrode current collector may be made of, for example, Cu, Ni, stainless steel, etc. Cu is more preferred because it is difficult to form an alloy with lithium and is easy to process into a thin film.
[0080] Examples of the method for producing the negative electrode sheet include a method of pressurizing and molding the negative electrode active material on the negative electrode current collector, a method of forming the negative electrode active material into a paste using an appropriate organic solvent, applying the paste to the negative electrode current collector, drying, and then pressing to fix the paste to the negative electrode current collector, etc. The paste preferably contains the conductive agent and the binder.
[0081] [Nonaqueous electrolyte] The non-aqueous electrolyte in one embodiment of the present invention is not particularly limited as long as it is a non-aqueous electrolyte generally used in non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries. As the non-aqueous electrolyte, for example, a non-aqueous electrolyte obtained by dissolving a lithium salt in an organic solvent can be used. As the lithium salt, for example, LiClO4, LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, Li2B 10 Cl 10 , lithium salts of lower aliphatic carboxylates, LiAlCl4, etc. The lithium salts may be used alone or in combination of two or more.
[0082] Examples of the organic solvent constituting the nonaqueous electrolyte include carbonates, ethers, esters, nitriles, amides, carbamates, sulfur-containing compounds, and fluorine-containing organic solvents obtained by introducing a fluorine group into these organic solvents. The organic solvents may be used alone or in combination of two or more.
[0083] [Method for manufacturing non-aqueous electrolyte secondary battery] A conventionally known manufacturing method can be used as the manufacturing method of the nonaqueous electrolyte secondary battery. For example, the positive electrode, the above-mentioned separator, and the negative electrode are arranged in this order to form the nonaqueous electrolyte secondary battery member. Next, the nonaqueous electrolyte secondary battery member is placed in a container that will become the housing of the nonaqueous electrolyte secondary battery. Furthermore, the container is filled with a nonaqueous electrolyte, and then sealed while reducing the pressure. This allows the nonaqueous electrolyte secondary battery to be manufactured. EXAMPLES
[0084] [Evaluation method for evaluation items] [Adhesive strength] The evaluation was carried out according to the following procedure. 1. The laminated separator obtained in the examples or comparative examples was cut out (length: 80 mm x width: 27 mm). 2. The cut laminate separator was placed on a release paper with the adhesive side facing up, and the release paper was then placed on a polyurethane sheet. 3. A positive electrode (length: 50 mm × width: 20 mm), a glass epoxy plate, release paper, and a polyurethane sheet were laminated in this order on the laminated separator, thereby obtaining a laminate in which the polyurethane sheet, release paper, polyethylene film, adhesive layer, positive electrode, glass epoxy plate, release paper, and polyurethane sheet were laminated in this order. 4. The laminate was preheated by pressing at 90°C, 1 MPa, for 30 seconds, and then pressed at 90°C, 6 MPa, for 10 seconds to bond the laminate. 5. The polyethylene film, adhesive layer, positive electrode and glass epoxy plate were taken out, and the positive electrode and glass epoxy plate were fixed together with double-sided tape. 6. The edge of the laminated separator was pulled so that the angle between the positive electrode and the laminated separator was 180°, and the maximum tensile strength at which it was peeled off was recorded as G1 (N). 7. The value obtained by dividing the G1 value by the width of the positive electrode (0.02 m) was determined as the adhesive strength (N / m) between the adhesive layer and the positive electrode.
[0085] [Heating shape retention rate] The measurement was carried out according to the following procedure. 1. The laminate separator obtained in the examples or comparative examples was cut into a square sample measuring 80 mm x 80 mm, with each side of the square parallel to either the MD or TD. 2. A line was drawn on the inside of the perimeter of the 80mm x 80mm, and a 60mm x 60mm square was drawn. At this time, the lines were drawn so that each side of the square was parallel to either the MD or TD direction. The square was drawn on the surface of the adhesive layer. 3. The sample sandwiched between pieces of paper was placed in an oven heated to 130°C and left to stand for 1 hour. 4. The sample was removed from the oven. The length of the sides of the square drawn on the sample was measured with a digital caliper. 5. The deformation in the MD direction of the sample after heating is called D MD This value was taken as the heat shape retention rate. MD is the length (mm) of a line parallel to the MD direction in a square drawn on the sample after heating.
[0086] In this specification, the term "MD direction" refers to the conveying direction in the production of a long film, and the term "TD direction" refers to the direction parallel to the surface of the long film and perpendicular to the MD direction.
[0087] [Synthesis Example 1: Synthesis of Block Copolymer (1)] Block copolymer (1) was synthesized by the following procedure. Block copolymer (1) has a wholly aromatic polyamide block and a semi-aromatic polyamide block. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 450 g of N-methylpyrrolidone was charged into a flask. 34 g of calcium chloride (dried at 200°C for 2 hours) was added, and the temperature was raised to 100°C to completely dissolve the calcium chloride. This resulted in a calcium chloride solution. The calcium chloride concentration in the calcium chloride solution was 7.1% by weight. The moisture content in the calcium chloride solution was adjusted to 430 ppm. 3. 2.94 g of paraphenylenediamine was added to the calcium chloride solution and completely dissolved by stirring for 30 minutes. During this process, the liquid temperature was maintained at 25°C. 4. The liquid temperature was cooled to 20°C. Then, 5.30 g of terephthalic acid dichloride was added and reacted for 1 hour. In this way, block A composed of poly(paraphenylene terephthalamide) was synthesized. 5. The liquid temperature was raised to 40° C. Then, 3.18 g of hexamethylenediamine was added and completely dissolved over one hour. 6. The liquid temperature was cooled to 20°C. Then, 5.64 g of terephthalic acid dichloride was added and reacted for 1.5 hours. In this way, block B composed of a polymer of hexamethylenediamine and terephthalic acid dichloride was extended to both ends of block A. At the end of the synthesis reaction, the content of block copolymer (1) in the polymerization liquid was 2.6% by weight.
[0088] Block copolymer (1) is a block copolymer in which block A, which is a wholly aromatic polyamide, and block B, which is a semi-aromatic polyamide, are linked in the order BAB. Of all the units in block copolymer (1), block A accounted for 48 mol%, and block B accounted for 52 mol%. Calculating from the amount of monomer charged, the number of paraphenylene terephthalamide units per block A was 51.
[0089] [Synthesis Example 2: Synthesis of Block Copolymer (2)] Block copolymer (2) was synthesized by the following procedure. Block copolymer (2) has a wholly aromatic polyamide block and a semi-aromatic polyamide block. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 268 g of N-methylpyrrolidone was charged into a flask. 20 g of calcium chloride (dried at 200°C for 2 hours) was added, and the temperature was raised to 100°C to completely dissolve the calcium chloride. This resulted in a calcium chloride solution. The calcium chloride concentration in the calcium chloride solution was 7.1% by weight. The moisture content in the calcium chloride solution was adjusted to 410 ppm. 3. 1.89 g of paraphenylenediamine was added to the calcium chloride solution and completely dissolved by stirring for 30 minutes. During this process, the liquid temperature was maintained at 25°C. 4. The liquid temperature was cooled to 20°C. Then, 3.41 g of terephthalic acid dichloride was added and reacted for 1 hour. In this way, block A composed of poly(paraphenylene terephthalamide) was synthesized. 5. The liquid temperature was raised to 40° C. Then, 2.60 g of 1,2-bis(2-aminoethoxy)ethane was added and completely dissolved over one hour. 6. The liquid temperature was cooled to 20°C. Then, 3.63 g of terephthalic acid dichloride was added and reacted for 1.5 hours. In this way, block C composed of a polymer of 1,2-bis(2-aminoethoxy)ethane and terephthalic acid dichloride was extended to both ends of block A. At the end of the synthesis reaction, the content of block copolymer (2) in the polymerization liquid was 3.0% by weight.
[0090] Block copolymer (2) is a block copolymer in which block A, which is a wholly aromatic polyamide, and block C, which is a semi-aromatic polyamide, are linked in the order of CAC. Of all the units in block copolymer (2), block A accounted for 45 mol%, and block C accounted for 55 mol%. Calculating from the amount of monomer charged, the number of paraphenylene terephthalamide units per block A was 51.
[0091] [Synthesis Example 3: Synthesis of Block Copolymer (3)] Block copolymer (3) was synthesized by the following procedure. Block copolymer (3) has a wholly aromatic polyamide block and an aliphatic polyamide block. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 179 g of N-methylpyrrolidone was charged into a flask. 14 g of calcium chloride (dried at 200°C for 2 hours) was added, and the temperature was raised to 100°C to completely dissolve the calcium chloride. This resulted in a calcium chloride solution. The calcium chloride concentration in the calcium chloride solution was 7.1% by weight. The moisture content in the calcium chloride solution was adjusted to 530 ppm. 3. 1.36 g of hexamethylenediamine was added to the calcium chloride solution and completely dissolved by stirring for 30 minutes. During this process, the liquid temperature was maintained at 25°C. 4. The liquid temperature was cooled to 20°C. Then, 2.73 g of sebacic acid dichloride was added and reacted for 1 hour. In this way, block D composed of a polymer of hexamethylenediamine and sebacic acid dichloride was synthesized. 5. The liquid temperature was raised to 40° C. 1.26 g of paraphenylenediamine was added and completely dissolved over 1 hour. 6. The liquid temperature was cooled to 20°C. Then, 2.32 g of terephthalic acid dichloride was added and reacted for 1.5 hours. In this way, the block A composed of poly(paraphenylene terephthalamide) was extended to both ends of the block D. At the end of the synthesis reaction, the content of the block copolymer (3) in the polymerization liquid was 2.9% by weight.
[0092] Block copolymer (3) is a block copolymer in which block A, which is a wholly aromatic polyamide, and block D, which is an aliphatic polyamide, are linked in the order ADA. Of all the units in block copolymer (3), block A accounted for 46 mol%, and block D accounted for 54 mol%. Calculated from the amount of monomer charged, the number of paraphenylene terephthalamide units per molecule of block copolymer (3) was 112.
[0093] [Synthesis Example 4: Synthesis of Block Copolymer (4)] Block copolymer (4) was synthesized by the following procedure. Block copolymer (4) has a wholly aromatic polyamide block and an aliphatic polyamide block. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 177 g of N-methylpyrrolidone was charged into a flask. 14 g of calcium chloride (dried at 200°C for 2 hours) was added, and the temperature was raised to 100°C to completely dissolve the calcium chloride. This resulted in a calcium chloride solution. The calcium chloride concentration in the calcium chloride solution was 7.1% by weight. The moisture content in the calcium chloride solution was adjusted to 400 ppm. 3. 1.63 g of 1,2-bis(2-aminoethoxy)ethane was added to the calcium chloride solution and completely dissolved by stirring for 30 minutes. During this process, the liquid temperature was maintained at 25°C. 4. The liquid temperature was cooled to 20°C. Then, 2.57 g of sebacic acid dichloride was added and reacted for 1 hour. In this way, block E composed of a polymer of 1,2-bis(2-aminoethoxy)ethane and sebacic acid dichloride was synthesized. 5. The liquid temperature was raised to 40° C. 1.19 g of paraphenylenediamine was added and completely dissolved over 1 hour. 6. The liquid temperature was cooled to 20°C. Then, 2.20 g of terephthalic acid dichloride was added and reacted for 1.5 hours. In this way, the block A composed of poly(paraphenylene terephthalamide) was extended to both ends of the block E. At the end of the synthesis reaction, the content of the block copolymer (4) in the polymerization liquid was 2.92% by weight.
[0094] Block copolymer (4) is a block copolymer in which block A, which is a wholly aromatic polyamide, and block E, which is an aliphatic polyamide, are linked in the order of AEA. Of all the units in block copolymer (4), block A accounted for 43 mol%, and block D accounted for 57 mol%. Calculated from the amount of monomer charged, the number of paraphenylene terephthalamide units per molecule of block copolymer (4) was 103.
[0095] [Synthesis Example 5: Synthesis of Resin 1] Resin 1 was synthesized by the following procedure. Resin 1 is polyparaphenylene terephthalamide and has the same structure as block A. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 418 g of N-methylpyrrolidone was placed in a flask. 31 g of calcium chloride (dried at 200°C for 2 hours) was then added and the temperature was raised to 100°C. 3. After calcium chloride was completely dissolved, the temperature of the solution was returned to room temperature, and then 13.2 g of paraphenylenediamine was added and completely dissolved. 4. While maintaining the temperature of the solution at 20±2°C, a total of 24.2 g of terephthalic acid dichloride was added in three portions. 5. The temperature of the obtained solution was kept at 20±2°C and the solution was aged for 1 hour to obtain a polymerization solution containing Resin 1.
[0096] A portion of the polymerization liquid of Resin 1 was sampled and water was added to precipitate Resin 1. When this sample was measured, the intrinsic viscosity of Resin 1 was found to be 1.9 dL / g.
[0097] [Synthesis Example 6: Block Copolymer (5)] Block copolymer (5) was synthesized by the following procedure. Block copolymer (5) has a wholly aromatic polyamide block and an aliphatic polyurea block. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 450 g of N-methylpyrrolidone was charged into a flask. 34 g of calcium chloride (dried at 200°C for 2 hours) was added, and the temperature was raised to 100°C to completely dissolve the calcium chloride. This resulted in a calcium chloride solution. The calcium chloride concentration in the calcium chloride solution was 7.1% by weight. The moisture content in the calcium chloride solution was adjusted to 130 ppm. 3. 19.23 g of O,O'-bis(2-aminopropyl)polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol (Jeffamine® ED-2003, manufactured by HUNTSMAN) was added and allowed to completely dissolve for 1 hour. 4. The liquid temperature was cooled to 20°C. Then, 1.78 g of hexamethylene diisocyanate was added and reacted for 1 hour. In this way, block F composed of a polymer obtained by a condensation reaction of O,O'-bis(2-aminopropyl)polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol and hexamethylene diisocyanate was synthesized. 5. The liquid temperature was raised to 40° C. 6.44 g of paraphenylenediamine was added and completely dissolved over 1 hour. 6. The liquid temperature was cooled to 20°C. Then, 11.91 g of terephthalic acid dichloride was added and reacted for 1.5 hours. In this manner, a block copolymer (5) was synthesized in which block F composed of a polymer obtained by a condensation reaction of O,O'-bis(2-aminopropyl)polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol with hexamethylene diisocyanate and block A composed of poly(paraphenylene terephthalamide) were linked by an amide bond. At the end of the synthesis reaction, the content of block copolymer (5) in the polymerization liquid was 7.0% by weight.
[0098] Block copolymer (5) is a block copolymer in which block A, which is a wholly aromatic polyamide, and block F, which is an aliphatic polyurea, are linked in the order of AFA. Block F accounted for 60 mol% of all units in block copolymer (5), and block A accounted for the remaining 40 mol%. The number of paraphenylene terephthalamide units per molecule of copolymer (5), calculated from the amount of monomer charged, was 129.
[0099] [Synthesis Example 7: Synthesis of block copolymer (6)] Block copolymer (6) was synthesized by the following procedure. Block copolymer (6) has a wholly aromatic polyamide block and an aliphatic polyurea block. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 450 g of N-methylpyrrolidone was charged into a flask. 34 g of calcium chloride (dried at 200°C for 2 hours) was added, and the temperature was raised to 100°C to completely dissolve the calcium chloride. This resulted in a calcium chloride solution. The calcium chloride concentration in the calcium chloride solution was 7.1% by weight. The moisture content in the calcium chloride solution was adjusted to 230 ppm. 3. 9.45 g of 1,2-bis(2-aminoethoxy)ethane was added to the calcium chloride solution and completely dissolved by stirring for 30 minutes. During this process, the liquid temperature was maintained at 25°C. 4. The liquid temperature was cooled to 20°C. Then, 10.64 g of hexamethylene diisocyanate was added and reacted for 1 hour. In this way, block G composed of a polymer of 1,2-bis(2-aminoethoxy)ethane and hexamethylene diisocyanate was synthesized. 5. The liquid temperature was raised to 40° C. 6.90 g of paraphenylenediamine was added and completely dissolved over 1 hour. 6. The liquid temperature was cooled to 20°C. Then, 12.60 g of terephthalic acid dichloride was added and reacted for 1.5 hours. In this manner, a block copolymer (6) was synthesized in which a block G composed of a polymer of 1,2-bis(2-aminoethoxy)ethane and hexamethylene diisocyanate and a block A composed of poly(paraphenylene terephthalamide) were linked by an amide bond. At the end of the synthesis reaction, the content of the block copolymer (6) in the polymerization liquid was 7.0% by weight.
[0100] Block copolymer (6) is a block copolymer in which block A, which is a wholly aromatic polyamide, and block G, which is an aliphatic polyurea, are linked in the order of AGA. Of all the units in block copolymer (6), block G accounted for 50 mol%, and block A accounted for the remaining 50 mol%. The number of paraphenylene terephthalamide units per molecule of copolymer (6), calculated from the amount of monomer charged, was 72.
[0101] [Synthesis Example 8: Synthesis of Resin 4] Resin 4 was synthesized by the following procedure. Resin 4 is a polymer of hexamethylenediamine and terephthalic acid dichloride, and has the same structure as block B. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 418 g of N-methylpyrrolidone was placed in a flask. 31 g of calcium chloride (dried at 200°C for 2 hours) was then added and the temperature was raised to 100°C. 3. After calcium chloride was completely dissolved, the temperature of the solution was returned to room temperature, and then 13.2 g of paraphenylenediamine was added and completely dissolved. 4. While maintaining the temperature of the solution at 20±2°C, a total of 24.2 g of terephthalic acid dichloride was added in three portions. 5. The temperature of the obtained solution was kept at 20±2° C. and the solution was aged for 1 hour to obtain a polymerization solution containing Resin 4.
[0102] A part of the polymerization liquid containing Resin 4 was collected and water was added to precipitate a sample of Resin 4. When this sample was used for measurement, the intrinsic viscosity of Resin 4 was found to be 1.9 dL / g.
[0103] Example 1 1. The polymerization liquid obtained in Synthesis Example 1 was mixed with N-methylpyrrolidone. The mixed amounts were 38 g of the polymerization liquid obtained in Synthesis Example 1 and 0.5 g of N-methylpyrrolidone. 2. Aluminum oxide (average particle size: 0.013 μm) was added to the obtained mixture and uniformly dispersed using a pressure type disperser. In this way, a coating liquid was prepared. The solid content concentration of the coating liquid (total concentration of the block copolymer and aluminum oxide) was 5 wt %. The amount of aluminum oxide used was 1 g. 3. Polyethylene porous film (thickness: 10 μm, weight per unit area: 5.7 g / m 2 ) was coated with Coating Liquid 1. In this manner, a coated product was obtained. 4. The obtained coating was treated in an oven at 50°C and humidity of 70% for 2 minutes. This resulted in the formation of an adhesive layer 1 on the polyethylene porous film. Thereafter, the adhesive layer 1 was washed with water and dried, and a laminated separator 1 provided with the adhesive layer 1 was obtained.
[0104] Example 2 A laminated separator 2 was obtained by carrying out the same operations as in Example 1, except that the polymerization liquid obtained in Synthesis Example 2 was used.
[0105] Example 3 A laminated separator 3 was obtained by carrying out the same operations as in Example 1, except that the polymerization liquid obtained in Synthesis Example 3 was used.
[0106] Example 4 A laminated separator 4 was obtained by carrying out the same operations as in Example 1, except that the polymerization liquid obtained in Synthesis Example 4 was used.
[0107] Example 5 1. The polymerization solution obtained in Synthesis Example 6 was mixed with N-methylpyrrolidone. This resulted in a solution in which the polymer was dissolved. The amount of the polymerization solution obtained in Synthesis Example 6 used was 14.3 g, and the amount of N-methylpyrrolidone used was 24.6 g. 2. Aluminum oxide (average particle size: 0.013 μm) was added to the mixture obtained in step 1, and uniformly dispersed using a pressure type disperser. This resulted in the preparation of a coating liquid. The solid content concentration of the coating liquid (total concentration of the block copolymer and aluminum oxide) was 5% by weight. The amount of aluminum oxide used was 1 g. 3. Polyethylene porous film (thickness: 10 μm, weight per unit area: 5.7 g / m 2 ) was coated with the coating liquid. In this manner, a coated product was obtained. 4. The coated product obtained in step 3 was treated in an oven at 50°C and humidity of 70% for 2 minutes. This resulted in the formation of an adhesive layer 7 on the polyethylene porous film. Thereafter, the adhesive layer 7 was washed with water and dried to obtain a laminated separator 7 provided with the adhesive layer 7.
[0108] Example 6 A laminated separator 8 was obtained by carrying out the same operations as in Example 5, except that the polymerization liquid obtained in Synthesis Example 7 was used.
[0109] Comparative Example 1 A laminated separator C1 was obtained in the same manner as in Example 1, except that the polymerization liquid containing Resin 1 of Synthesis Example 5 was used as the coating liquid.
[0110] Comparative Example 2 The same operations as in Example 5 were carried out except that the polymerization liquid obtained in Synthesis Example 8 was used, to obtain a laminated separator C2.
[0111] 〔result〕 The results are shown in Table 1. [Table 1]
[0112] As can be seen from Table 1, the laminate separators C1 and C2 did not adhere to the positive electrode. In contrast, the laminate separators 1 to 6 were able to adhere to the positive electrode. As can be seen from these results, sufficient adhesion can be achieved by blending a block copolymer having a structure in which a block mainly composed of a wholly aromatic polyamide is linked to a block mainly composed of a non-wholly aromatic polyamide or polyurea. The heat resistance of the laminate separators 1 to 6 was comparable to that of Comparative Examples 1 and 2, which correspond to the prior art. [Industrial Applicability]
[0113] The present invention can be used for non-aqueous electrolyte secondary batteries and the like.
Claims
1. A block copolymer having a block A mainly composed of a unit represented by the following formula (1) and a block B mainly composed of a unit represented by the following formula (2a) and / or formula (2b): -(NH-Ar1-NHCO-Ar2-CO)- Formula (1) -(NH-B1-NHCO-B2-CO)- Formula (2a) -(NH-B3-NHCONH-B4-NHCO)- Formula (2b) In formula (1), Between different units, the structures of Ar1 and Ar2 may be different. Ar1 and Ar2 each independently represent a divalent group having one or more aromatic rings, In formula (2a), Between different units, the structures of B1 and B2 may be different, At least one of B1 and B2 is a divalent group not having an aromatic ring, In formula (2b), Between different units, the structure of each of B3 and B4 may be different, At least one of B3 and B4 is a divalent group not having an aromatic ring.
2. 2. The block copolymer according to claim 1, wherein the proportion of the block A in the entire block copolymer molecule is 10 to 70 mol %.
3. 2. The block copolymer according to claim 1, wherein the proportion of the block B in the entire block copolymer molecule is 30 to 90 mol %.
4. An adhesive layer for a non-aqueous electrolyte secondary battery, comprising the block copolymer according to claim 1 .
5. The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 4 , further comprising a filler.
6. 5. A laminate separator for a non-aqueous electrolyte secondary battery, comprising the adhesive layer for a non-aqueous electrolyte secondary battery according to claim 4 laminated on one or both sides of a polyolefin porous film.
7. A positive electrode and The adhesive layer for a nonaqueous electrolyte secondary battery according to claim 4 ; A negative electrode; are laminated in this order.
8. A positive electrode and The laminate separator for a nonaqueous electrolyte secondary battery according to claim 6 ; A negative electrode; The above are laminated in this order.
9. A nonaqueous electrolyte secondary battery comprising the adhesive layer for a nonaqueous electrolyte secondary battery according to claim 4 or 5, the laminate separator for a nonaqueous electrolyte secondary battery according to claim 6, or the member for a nonaqueous electrolyte secondary battery according to claim 7 or 8.
Citation Information
Patent Citations
Partition wall panel
JP2006299612A